Rates of Negative Conversion and Relapse of High-risk Human Papillomavirus Genotypes in Cervical Infection - Moo-Sang CHONG; Wonseo PARK; Kyutaeg LEE (Korean Journal of Clinical Laboratory Science)
Cervical cancer is a major health issue globally. High-risk human papillomavirus (Hr HPV) infections, such as HPV16/18, play a crucial role in the cause of cervical cancer. Ninety percent of HPV infections are cleared or become inactive within 12 to 24 months of exposure to the virus. On the other hand, there are a few reports about the persistence of Hr HPV according to each genotype, which increases the risk of progression to cervical cancer. Therefore, this study analyzed the negative conversion rates and the relapse rates according to each Hr HPV genotype in Hr-HPV cervical infections. The negative conversion rate of Hr HPV averaged 53.0% for five years and decreased with the number of infected HPV genotypes. The time to negative conversion increased with the number of infected HPV genotypes and varied with age and genotypes in single-infected patients. The relapse rates averaged 10.7% for five years, decreased with the number of infected HPV genotypes, and the time to relapse decreased with the number of infected HPV genotypes. The rates of relapse with the same genotype varied according to the genotype. These results can be used as an adjunct to prognostic estimates of the cure and recurrence rates in HPV-infected individuals.